(Un)seen Undulation: Reflecting on the Ripples made by Artist-Teachers and Researchers - Vincent, Adam (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2020)
This Artistic and Creative Inquiry (ACI) uses personal narrative to share examples of how poetry has been successfully used in both classroom and academic support settings to enhance students’ understanding of course concepts and to identity their own learning preferences. This pragmatic discussion of poetry as a teaching tool is then coupled with a poetic exploration of artist-teacher identity and how this identity influences teaching approaches. The inquiry concludes with a discussion of the power that exists when there is an awareness and ownership of the role of artist-teacher (and researcher) and the impacts that it can have on students and ultimately society.